Geographic network characteristics of venture capital firms and high-tech enterprise innovation: evidence from high-speed rail - Ningyue Liu; Tailun Chen; Huijuan Cao (Humanities & Social Sciences Communications)
Abstract Combining both quantitative and qualitative methods, this study examines the influence of the geographic network characteristics of venture capital (VC) firms on corporate innovation. Using data on 402 Chinese firms listed on the SSE STAR Market during their pre-IPO period (2001–2019), we empirically find that high-speed rail (HSR) connections between VC firms and investee firms during the post-investment stage significantly enhance the innovation performance of the investee firms. Mechanism analyses attribute this effect to improved knowledge transfer from VCs to investees. We further find that the impact is most pronounced when HSR is more convenient than air travel and when firms exhibit strong innovation incentives. These findings underscore the role of HSR in strengthening VC networks, facilitating knowledge exchange, and enhancing innovation performance.